Nanocarbon electronics - Zhou, Changjin; Zhang, Min; Yang, Cary Y (Jenny Stanford Publishing, 2021)
This book presents a comprehensive review of research on applications of carbon nanotubes (CNTs) and graphene to electronic devices. As nanocarbons in general, and CNTs and graphene in particular, are becoming increasingly recognized as the most promising materials for future generations of electronic devices, including transistors, sensors, and interconnects, a knowledge gap still exists between the basic science of nanocarbons and their feasibility for cost-effective product manufacturing. The book highlights some of the issues surrounding this missing link by providing a detailed review of the nanostructure and electronic properties, materials, and device fabrication and of the structure-property-application relationships.